Peran Orang Tua Sebagai Guru Dengan Perkembangan Perilaku Sosial Pada Anak Usia Prasekolah (4-6 Tahun) Di TK Al-Ikhlas Desa Sukoanyar Dusun Toyorono Kecamatan Ngoro Kabupaten Mojokerto - Lukman Arifin , Tripeni (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2013)
Child’s social behavior and attitudes reflect the child received treatment at home. Mothers was instrumental in monitoring the development of social behavior in preschool children, where preschool is the year – the first yaer of life a child learn to socialize. The purpose of this study is to determine the relationship parent role as a teacher with the development of social behavior in preschool children (4 -6 years) in TK AL-IKHLAS Sukoanyar Village Toyorono Hamlet Ngoro District Mojokerto Regency. This study population uses the cross sectional design with analytic coleration approach. The study population was all parent who have preschool children (4-6 years) in TK AL-IKHLAS Sukoanyar Village Toyorono Hamlet Ngoro District Mojokerto Regency as many as 37 people taken to with sampling is 34 people for research to the purposive sampling techniques. Variable research is the role of parents and development of social behavior in preschool children (4-6 years). Data were collected using questionnaires and observation sheet instruments, after the collected data were analyzed using Mann Whitney test. Mann Whitney test result with critical rejection region α = 0,05 to obtain the probability calculation (p) = 0,009 so 0,009 < 0,05, which means there is a relationship role of parents as teachers with the development of social behavior in preschool children (4-6 years) in TK AL-IKHLAS Sukoanyar Village Toyorono Hamlet Ngoro District Mojokerto Regency. Based on these studies it is known that a child will be able to undergo normal development in a task if the parent always gives the task of continous development of the child.